Trademark according to islamic perspective - Naziree, Md Yusof; Nor Aida, Ab. Kadir (2018)
The position of intellectual property has been approved by Islam. The development of latest technology shows the diversity products that could only be assessed by the expertise. A product which is in a small item but once it is commercialized, it will bring a huge returns. Hence, this study will briefly discuss the concept of property according to Islam and intellectual property in general. Then the main focus on the dangers will be seen as far as conforming to Islamic muamalat transactions. Existing provisions of the law will also be discussed to see the compatibility of the application from the Islamic perspective